Functional morphology of the Ordovician plectambonitoid brachiopod Inversella ( Reinversella ) arancibiai Herrera & Benedetto from the San Juan Formation, Argentine Precordillera - Benedetto, Juan Luis Arnaldo (2008)
New well-preserved material of the plectambonitoid brachiopod Inversella (Reinversella) arancibiai Herrera & Benedetto, 1987 collected from the San Juan Formation (Darriwilian, Middle Ordovician) of the Argentine Precordillera is described and illustrated, allowing a better understanding of its functional morphology. Inversella (Reinversella) is one of the earliest known brachiopods to develop a geniculate shell. Adult specimens of I. (R.) arancibiai have an open delthyrium indicating attachment throughout life. We infer that juvenile specimens lacking geniculation lived umbo-down and that development of geniculation could reflect a progressive change in mode of life from erect to reclined. The posterior thickening of valves indicates a life position with the umbonal region sunk in the substrate and the trail orientated in a subvertical position. Since open shelf settings inhabited by I. (R.) arancibiai have low sedimentation rates, it seems improbable that geniculation was an adaptation to counter shell burial. Its function was most probably to separate exhalant and inhalant currents. We hypothesize that the deep channel developed along the periphery of the ventral valve functioned as a collector of waste waters towards the posterolateral regions of the shell where exhalant currents were expelled.